Pelatihan Aplikasi Canva untuk Membantu Kinerja Pegawai di Kecamatan Galesong Utara Kabupaten Takalar - Israwati Hamsar; Dessy Ana Laila Sari; Rosidah; Dyah Darma Andayani; B, Muhammad Fajar; Wahyudi; Andi Baso Kaswar (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Training in the use of Canva application to assist employee performance is a program aimed at enhancing employees' graphic design skills using Canva. This training provides benefits for beginners who want to learn graphic design with user-friendly features and ready-to-use templates. Research also indicates that Canva application training has a positive impact on employee performance. Therefore, a socialization of Canva application training is conducted at the Office of North Galesong District, Takalar Regency to assist employees in improving their graphic design competence and performance. The implementation method of this activity involves collaboration with relevant parties, field surveys, training material preparation, socialization, workshops, evaluation, and visits to participants. The results and discussion of this activity encompass preparation, administration, counseling, and delivery of materials. Supporting factors in this activity include participants' interest and willingness, as well as interactions with the resource persons. However, there are inhibiting factors such as participants' initial lack of understanding of the Canva application, which can be overcome by providing detailed explanations. From this activity, it can be concluded that the socialization of Canva application usage is essential for enhancing employee performance in graphic design. Participants are expected to apply the training materials, leading to an improvement in knowledge, graphic design performance, and the dissemination of engaging information for the community in North Galesong District.